Analysis of Readiness and Acceptance Levels of the 'Customer Monitoring Apps' Technology in the Heavy Equipment Industry Using the Technology Readiness and Acceptance Model (TRAM) - Saputra, Edo; Puspita, Niniek Fajar; Rahardjo, Jani (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to analyze the technology readiness and technology acceptance rate of UT Connect application users in the heavy equipment industry using the Technology Readiness and Acceptance Model (TRAM) approach. The analysis was carried out through the Structural Equation Modeling – Partial Least Square (SEM–PLS) method, including testing the outer model, inner model, and conducting hypothesis testing to assess validity, reliability, and relationships between constructs. The results of the study showed that all constructs met the criteria for validity and reliability. In terms of technological readiness, Optimism has a significant effect on Perceived Usefulness, while Innovativeness, Discomfort, and Insecurity have no effect on either Perceived Usefulness or Perceived Ease of Use. These findings indicate that users have a good level of readiness to embrace digital innovations, even though negative factors do not have a significant influence. Regarding technology acceptance, the variables Perceived Enjoyment, Technology Self-Efficacy, Perceived Ease of Use, and Perceived Usefulness have a significant influence on user attitudes (Attitude Toward Using) and actual usage behavior (Actual Usage). The relationship between Perceived Ease of Use and Perceived Usefulness was also found to be strong, and users’ positive attitudes have an effect on their use of the application. The findings of this study provide empirical evidence that the TRAM model can explain the factors influencing the acceptance and use of digital applications and can serve as a basis for enhancing the effectiveness of UT Connect implementation.